Cognitive, Morbid and Premorbid Factors in the Development and Maintenance of Paranormal Beliefs - Pérez Navarro, José Miguel (Interdisciplinaria, 2021)
Paranormal beliefs, regardless of their veracity, clearly constitute an important dimension of human psychology. Survey work across the world reveals that around 50 % of people hold at least one paranormal belief. This figure is surprisingly high considering the lack of robust scientific evidence in support of the referred phenomena, and suggests the existence of resilient psychological mechanisms at the basis of the development and maintenance of such beliefs. Researchers in the area have proposed a diversity of explanations, exploring a large number of individual factors. However, despite the generous effort, we have not been able to develop a comprehensive explanatory model capable of accommodating the body of empirical findings. With this study we aimed to contribute towards a better understanding of paranormal belief as a multicausal phenomenon. In order to achieve this, we explored a set of variables related to the main perspectives in the literature. We used a sample of 184 subjects of very diverse nationalities, ages, and cultural backgrounds. We surveyed paranormal beliefs among our participants and observed that 71 % of the sample showed traditional religious beliefs, 34 % believed in psychic phenomena such as extrasensory perception or psychokinesis, 31 % in superstition, 23 % in witchcraft, and 39 % in anomalous natural phenomena such as astrology or extraordinary life forms. Eighty four per cent of the subjects responded positively to at least one of the 26 items of paranormal beliefs evaluated in the scale. A correlation analysis was conducted between the individuals' traits and paranormal belief scores. Schizotypy (rxy = .23, p < .001), unusual experiences (rxy = .37, p < .001), introvertive anhedonia (rxy = .28, p < .001), conditional reasoning in tasks with paranormal content (rxy = .23, p = .001), need for affiliation (rxy = .21, p < .002), and report of subjective extraordinary experiences (rxy = .35, p < .001) correlated significantly with belief in the paranormal. These results are consistent with Russell and Jones' (1980) theory of compensation of basic needs and suggest that paranormal belief may rise in combination with premorbid signs of psychopathology. However, they suggest that belief in the paranormal may not be a consequence of a cognitive deficit in this type of reasoning. A multiple regression analysis revealed a five variable solution. In the equation, subjective extraordinary experiences, unusual experiences (from the schizotypy scale), need for autonomy, need for achievement, and introvertive anhedonia contributed standardized coefficients of .3, .23, .24, .22 and .13 respectively. The model explained 27 % of the variance. The findings of this study are consistent with a multicausal conception of paranormal belief. A model is proposed in which paranormal beliefs can stem from a variety of factors and, as they develop, a reciprocal interaction between experience and belief arises, contributing to their definitive accommodation in the individual's psychology. The identification and exploration of contributing factors to the development and maintenance of the paranormal belief has been very fruitful in the last decades. In addition, the explanatory hypotheses raised by the researchers do not seem to be mutually exclusive. Therefore, the simultaneous consideration of these could be a successful approach in future studies. The elaboration of an explanatory model that contemplates both the multicausality and the multidimensionality of the phenomenon could provide a qualitative leap in the area.
Keywords: needs; paranormal belief; reasoning; schizotypy; subjective extraordinary experience; Scopus